Design of portable industrial automation education training kit compatible for IR 4.0 - Khairudin A.R.M.; Abu-Samah A.; Aziz N.A.S.; Azlan M.A.F.M.; Karim M.H.A.; Zian N.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Automation; Computer software; Curricula; Students; Teaching; Education training; Industrial automation; Industrial revolutions; Programmable logic controllers (PLC); Sensor applications; Sensors and actuators; Simulation software; Teaching and learning; Process control